2020
DOI: 10.5540/03.2020.007.01.0419
|View full text |Cite
|
Sign up to set email alerts
|

Principais fatores que influenciam a Desigualdade de Gêneros no Mundo

Abstract: Resumo. A desigualdade de gênerosé um assunto que vêm ganhando notoriedade naś ultimas décadas e tem sido alvo de grandes discussões, principalmente após os movimentos feministas. OÍndice de Desigualdade de Gêneros (IDG) mostra a perda de potencial no desenvolvimento humano devidoà desigualdade entre realizações femininas e masculinas em diversas dimensões sociais. A igualdade de gênero contribui para a eficiência econômica e a obtenção de outros resultados essenciais de desenvolvimento, tendo assim uma influê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As it is extensively described in the literature, the conditions of the migratory process and the social, structural, and cultural factors inherent to it may be strong predictors for the multiple victimization of immigrant women in the receiving countries (Annoni, 2020;Gonçalves & Fonseca, 2020;Marchetti, 2018;Ramos, 2021;Silva et al, 2020). This concept of multiple victimization emerges in the literature in the 80s (Sparks, 1981) and, even though it is a concept of difficult consensus, it shows that one type of violence is almost always associated with others and that a single experience of a type of abuse rarely occurs (Caridade et al, 2019).…”
Section: Antecedents For Understanding the Experience Of Violent Inti...mentioning
confidence: 99%
See 1 more Smart Citation
“…As it is extensively described in the literature, the conditions of the migratory process and the social, structural, and cultural factors inherent to it may be strong predictors for the multiple victimization of immigrant women in the receiving countries (Annoni, 2020;Gonçalves & Fonseca, 2020;Marchetti, 2018;Ramos, 2021;Silva et al, 2020). This concept of multiple victimization emerges in the literature in the 80s (Sparks, 1981) and, even though it is a concept of difficult consensus, it shows that one type of violence is almost always associated with others and that a single experience of a type of abuse rarely occurs (Caridade et al, 2019).…”
Section: Antecedents For Understanding the Experience Of Violent Inti...mentioning
confidence: 99%
“…Migration has proved to be a positive experience for millions of women and their families, as the displacement to a new country exposes women to new ideals and social norms that can promote their rights (Bastia & Piper, 2019). However, as many national and international studies have revealed, migration can reinforce the gender asymmetries and reproduce mechanisms of discrimination and oppression (Annoni, 2020;Cabecinhas, 2020;Gonçalves & Fonseca, 2020;Gonçalves & Matos, 2016;Silva, 2015), especially if integration policies are oriented exclusively towards accommodating the society of origin and satisfying the needs of the migratory purpose (Sousa, 2020).…”
Section: Introductionmentioning
confidence: 99%